Stevens-Johnson syndrome and toxic epidermal necrolysis: A systematic review of PubMed/MEDLINE case reports from 1980 to 2020 - Wang, Liqin; Varghese, Sheril; Bassir, Fatima; Lo, Ying-Chin; Ortega, Carlos A.; Shah, Sonam; Blumenthal, Kimberly G.; Phillips, Elizabeth J.; Zhou, Li (Frontiers in Medicine, 2022)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare, life-threatening immunologic reactions. Prior studies using electronic health records, registries or reporting databases are often limited in sample size or lack clinical details. We reviewed diverse detailed case reports published over four decades. Methods: SJS/TEN-related case reports were identified from the MEDLINE database between 1980 and 2020. Each report was classified by severity (i.e., SJS, TEN, or SJS-TEN overlap) after being considered a "probable" or "definite" SJS/TEN case. The demographics, preconditions, culprit agents, clinical course, and mortality of the cases were analyzed across the disease severity. Results: Among 1,059 "probable” or “definite" cases, there were 381 (36.0%) SJS, 602 (56.8%) TEN, and 76 (7.2%) SJS-TEN overlap cases, with a mortality rate of 6.3%, 24.4%, and 21.1%, respectively. Over one-third of cases had immunocompromised conditions preceding onset, including cancer (n=194,18.3%), autoimmune diseases (n=97, 9.2%), and human immunodeficiency virus (HIV) (n=52, 4.9%). During the acute phase of the reaction, 843 (79.5%) cases reported mucous membrane involvement and 210 (19.8%) involved visceral organs. Most cases were drug-induced (n=957, 90.3%). A total of 379 drug culprits were reported; the most frequently reported drug were antibiotics (n=285, 26.9%), followed by anticonvulsants (n=196, 18.5%), analgesics/anesthetics (n=126, 11.9%), and antineoplastics (n=120, 11.3%). 127 (12.0%) cases reported non-drug culprits, including infections (n=68, 6.4%), of which 44 were associated with a mycoplasma pneumoniae infection and radiotherapy (n=27, 2.5%). Conclusions: An expansive list of potential causative agents were identified from a large set of literature-reported SJS/TEN cases, which warrant future investigation to understand risk factors and clinical manifestations of SJS/TEN in different populations.